2020
DOI: 10.1186/s12967-020-02506-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging characteristics of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS): a systematic review

Abstract: Background: Since the 1990s, neuroimaging has been utilised to study Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), a debilitating illness with unknown aetiology. While brain abnormalities in ME/CFS have been identified, relatively little is known regarding which specific abnormalities are consistently observed across research groups and to what extent the observed abnormalities are reproducible. Method: To identify consistent and inconsistent neuroimaging observations in ME/CFS, this retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 93 publications
2
55
0
Order By: Relevance
“…Indeed, the dorsal brainstem is packed with nuclei governing symptoms such as dysautonomia, sleep problems, nausea, pain, and sickness ( Figure 5 ). Several studies have reported functional and structural brainstem abnormalities in ME/CFS ( Barnden et al, 2019 ; VanElzakker et al, 2019 ; Shan et al, 2020 ), including one study demonstrating brainstem glial activation positively correlated with cognitive impairment ( Nakatomi et al, 2014 ).…”
Section: Sars-cov-2 And/or Related Inflammatory Insults May Disrupt Brainstem Signalingmentioning
confidence: 99%
“…Indeed, the dorsal brainstem is packed with nuclei governing symptoms such as dysautonomia, sleep problems, nausea, pain, and sickness ( Figure 5 ). Several studies have reported functional and structural brainstem abnormalities in ME/CFS ( Barnden et al, 2019 ; VanElzakker et al, 2019 ; Shan et al, 2020 ), including one study demonstrating brainstem glial activation positively correlated with cognitive impairment ( Nakatomi et al, 2014 ).…”
Section: Sars-cov-2 And/or Related Inflammatory Insults May Disrupt Brainstem Signalingmentioning
confidence: 99%
“…Indeed, several teams have delineated the apparently inadequate communication in ME/CFS between the brainstem and upstream regions like the hypothalamus, hippocampus and prefrontal cortex -here again, the assumption of the brainstem as the tectonic epicenter may help explain the findings of widespread dysfunctions in other regulatory areas of the brain. 6,110 Question 2: With so many pathogenetic links clearly identified in ME/CFS research (including hypoperfusion, inflammation, abnormal adrenergic signaling etc.) -with which link could the pathogenetic chain in ME/CFS start?…”
Section: Discussionmentioning
confidence: 99%
“…13 Imaging studies in ME/CFS patients have shown multiple alterations in the prefrontal cortex, combined with neuroinflammation in the midbrain. 110,111 Experimental evidence suggests that the astroglial compartment is centrally involved in cognitive and memory dysfunctions. 112 Astrocytes seem to especially contribute to memory consolidation and seem to mediate the effects of vigilance and arousal on memory performance.…”
Section: Cognitive and Memory Impairmentmentioning
confidence: 99%
“…One study recognized nine biochemical factors common to both male and female ME/CFS patients but not healthy controls with an apparent diagnostic accuracy of more than 90% [19] Neuroimaging in ME/CFS shows more diffuse activation patterns than controls on attention tests, sometimes structural abnormalitis in the brain stem with signs of inflammation,reduction in the serotonin 1A receptor binding, particularly in the hippocampus bilaterally, and reduced serotonin transporters density in the rostral anterior cingulate [23].…”
Section: Patogenesismentioning
confidence: 99%